2007
DOI: 10.1614/ws-06-211r.1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Growth and Seed Properties in Introduced vs. Native Populations of Yellow Starthistle (Centaurea solstitialis)

Abstract: There is much discussion as to why a plant becomes invasive in a new location but is not problematic in its native range. One example is yellow starthistle, which originates in Eurasia and is considered a noxious weed in the United States. We grew yellow starthistle originating from native and introduced regions in a common environment to test whether differences in growth would be observed. In growth chamber studies, seedlings originating from the invasive range were larger than seedlings from the native rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 52 publications
(52 reference statements)
5
61
0
Order By: Relevance
“…Other studies indicate that local adaptation in seed and seedling size, seed morphology, and seed dormancy has occurred since the introduction of C. solstitialis into the United States (Widmer et al 2007;Hierro et al 2009). Such local adaptation and reproductive isolation might contribute to invasiveness (e.g., by fixing advantageous adaptations in the more adapted populations of the nonnative range), but since the noninvasive C. sulphurea also shows evidence of intercontinental reproductive isolation, isolation per se may be unlikely to explain invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies indicate that local adaptation in seed and seedling size, seed morphology, and seed dormancy has occurred since the introduction of C. solstitialis into the United States (Widmer et al 2007;Hierro et al 2009). Such local adaptation and reproductive isolation might contribute to invasiveness (e.g., by fixing advantageous adaptations in the more adapted populations of the nonnative range), but since the noninvasive C. sulphurea also shows evidence of intercontinental reproductive isolation, isolation per se may be unlikely to explain invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…However, Quin et al (2007) reported the same results when they performed greenhouse experiments to evaluate the competitive interactions between C. solstitialis and five herbaceous species natives to California grasslands. Widmer et al (2007) suggest that C. solstitialis success in California is not fully explained by its life history traits (i.e., prolific seed production, high seed viability, deep-root system, etc. ), because those traits are also present in its native range.…”
Section: Seed Germination Capability and Seed-seed Allelopathic Effectsmentioning
confidence: 99%
“…), because those traits are also present in its native range. In fact, Widmer et al (2007) showed that C. solstitialis has changed the resource allocation in the invaded range, since seeds have larger reserve of starch compared to its native range. As consequence, seedlings are larger in the invaded range and it could give these plants an early competitive advantage against native plants (Widmer et al 2007).…”
Section: Seed Germination Capability and Seed-seed Allelopathic Effectsmentioning
confidence: 99%
See 2 more Smart Citations